2017
DOI: 10.5696/2156-9614-7-13.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Air Pollutant Concentrations Near Major Roads in Residential, Commercial and Industrial Areas in Ibadan City, Nigeria

Abstract: Background.Urbanization, energy consumption, intensification of road traffic and rapid population growth pose significant challenges to ambient air quality. Therefore, regular monitoring of current air quality is essential.Objectives.The study investigated the concentration of sulfur dioxide (SO2), oxides of nitrogen (NOx), ozone (O3), ammonia (NH3) and carbon monoxide (CO) in ten different sites to investigate possible anthropogenic sources within Ibadan, Nigeria.Methods. Air samples were collected into speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…This approach involves mapping the geographical distribution of the disease against the distribution of climate variables, and carrying out a regression analysis to characterize the climatic conditions that are associated with presence vs. absence of disease, or with different levels of disease transmission [15]. The main advantage of this approach is that it is entirely driven by a transparent statistical relationship between climate and disease distributions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach involves mapping the geographical distribution of the disease against the distribution of climate variables, and carrying out a regression analysis to characterize the climatic conditions that are associated with presence vs. absence of disease, or with different levels of disease transmission [15]. The main advantage of this approach is that it is entirely driven by a transparent statistical relationship between climate and disease distributions.…”
Section: Methodsmentioning
confidence: 99%
“…It is also theoretically possible to include other, non-climatic, explanatory variables or confounders in the model, e.g. Ipeaiyeda et al [15] assessed and investigated the spatiotemporal relationship between dengue fever cases and climatic conditions of temperature and precipitation using Negative binomial regression a subset of bivariate analysis to discover that high temperature and low precipitation were the favourable condition for the spread of dengue virus in South East Florida over a period of 34 years. Lugo [16] examined the long-term trend of extreme temperatures, heat waves and cold spells in terms of frequency, intensity and duration over 1951-2015 and their potential association with El Niño Southern Oscillation (ENSO) events using Linear regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Spatio temporarily examined the impacts of land use on air quality in Wuhan China using buffering for the demarcations of sites, bivariate correlation to test for the relationship between land use variables and annual average concentrations of air pollutants, stepwise linear regressions for modeling and the Leave Out One Cross Validation (LOOCV) techniques to test for the performance of the regression model. In Nigeria, Ipeaiyeda and Adegboyega (2017) (2012) used anthropometric (weight (kg), height (m) and body mass index), Spiro metric (lung function capacities e.g. force vital capacity (FVC), air quality measures (Aerosol monitor 'DUST TRACK model 8520 (TS1 Inc., Minnesota, USA) and statistical techniques (descriptive analysis, analysis of variance (ANOVA), chi-square, and multiple logistic regressions) to test for the association between exposure to outdoor ambient air pollution and its risk factors.…”
Section: Air Quality Monitoringmentioning
confidence: 99%
“…These marked variation in sulpur(iv)oxide, nitrogen(iv)oxide and fine particulate matter over residential, commercial and industrial land uses is consistent with the findings of Superczynski and Sundar (2011) who investigated the impacts of land use land-cover changes on air quality in Alabama USA and discovered higher levels of pollutants over commercial and industrial areas than residential areas, Offor, et al (2016) who reviewed the concentration levels of particulate matter in Nigerian cities revealed high levels of pollutants in commercial than residential areas, Jenq-Hwan, et al (2017) who examine the impacts of particulate matter on tuberculosis cases in Taipei city Taiwan, noted that higher levels of particulate matter was responsible for the intensity of tuberculosis cases, who investigated the impacts of land use on air quality in Wuhan, China stated that land use is the precursor for elevated levels of pollutants and Ipeaiyeda, and Adegboyega (2017) investigation of the concentration levels of air pollutants along traffic corridors of Ibadan city discovered consistent elevated levels of pollutants across commercial areas than industrial and residential areas in Ibadan city.…”
Section: Sulfur (Iv) Oxide (So2) and Nitrogen Dioxide Levelsmentioning
confidence: 99%
“…Studies have indicated that vehicles are the major source of air pollution in most cities across the world [8]. [9] stated that the major reasons for the high level of vehicular emission are the large number of vehicles on congested streets, poor quality vehicles, poor quality fuels usage, maintenance systems and ineffective transport management and the use of two-smoke engine vehicles on the road.…”
Section: Introductionmentioning
confidence: 99%